Racial Differences in the Stability of High Earnings among Young Men - Loury, Linda Datcher (Journal of Labor Economics, 1986)
The proposition that there is a large and growing black middle class is a major tenet of much recent work on black economic progress. This paper examines one aspect of middle-class status for black families, namely, the stability of high earnings among young male household heads. It finds that while such men are much less likely to have high earnings than are their white counterparts, there are only small racial differences in the stability of high earnings over time. Copyright 1986 by University of Chicago Press.